2013
DOI: 10.1002/hep.26341
|View full text |Cite
|
Sign up to set email alerts
|

Portal hypertensive vaginal bleeding

Abstract: A 44-year-old woman with hepatitis C cirrhosis presented with a week of heavy vaginal bleeding. Her obstetric history was significant for three cesarean sections. Her gynecologist made an initial diagnosis of menometrorrhagia exacerbated by thrombocytopenia and coagulopathy. Computed tomography (CT) angiography revealed splenic vein thrombosis and engorged pelvic veins which arose as collaterals from the splenic vein ( Fig. 1). Hysteroscopy could not identify a culprit lesion due to the rapidity of bleeding.A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…A literature review revealed no previous reports of vaginal bleeding owing to PMVT. It has been postulated that the perturbation of the uterine plexus due to previous surgery leads to insu cient decompression of the vaginal venous plexus; this results in shunted blood ow into the systemic circulation, causing vaginal variceal bleeding [10]. However, this phenomenon was not observed in our patient.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…A literature review revealed no previous reports of vaginal bleeding owing to PMVT. It has been postulated that the perturbation of the uterine plexus due to previous surgery leads to insu cient decompression of the vaginal venous plexus; this results in shunted blood ow into the systemic circulation, causing vaginal variceal bleeding [10]. However, this phenomenon was not observed in our patient.…”
Section: Discussioncontrasting
confidence: 50%
“…Vaginal variceal bleeding complicated by portosystemic collateral pathways is very uncommon, and only eight such cases have been reported [10]. A literature review revealed no previous reports of vaginal bleeding owing to PMVT.…”
Section: Discussionmentioning
confidence: 99%